A Pilot Evaluation Assessing the Ease of Use and Accuracy of the New Self/Home-Tonometer IcareHOME in Healthy Young Subjects. Issue 10 (October 2016) - Noguchi, Asuka; Nakakura, Shunsuke; Fujio, Yuki; Fukuma, Yasuko; Mori, Etsuko; Tabuchi, Hitoshi; Kiuchi, Yoshiaki
Abstract : Purpose: We investigated the ease of use and accuracy of a new self/home-tonometer (IcareHOME) versus Goldmann applanation tonometry (GAT) and the Icare tonometer (Icare) by measuring the diurnal intraocular pressure (IOP). Patients and Methods: The right eyes of 43 healthy young subjects were studied. The IOP was measured using the IcareHOME, GAT, and Icare 6 times a day, every 2 hours, from 8:00 to 18:00. The coincidence of the diurnal curves among all tonometers was analyzed using a linear mixed model. The intradevice and interdevice agreement was evaluated using the intraclass correlation coefficients (ICC) and Bland-Altman method. The subjects' perception of the IcareHOME was evaluated using a questionnaire. Results: The liner mixed model showed similar diurnal IOP curves for all tonometers ( P =0.543); however, significant differences were observed between the tonometers over time ( P <0.001). The intradevice repeatability was ICC>0.8 among all tonometers, although the interdevice agreement was lowest between the IcareHOME and GAT (ICC=0.641). The IOP values were significantly lower for the IcareHOME than for the GAT at 12:00, 16:00, and 18:00 ( P <0.05, Tukey-Kramer test). The mean differences between the Icare and IcareHOME and GAT and IcareHOME were 0.83 and 1.03 mm Hg, respectively (95% limit of agreement: −4.17 to 5.84 mm Hg and −3.91 to 5.98 mm Hg, respectively). Regarding the subjects' perception of handling the IcareHOME, 17 (39.5%) subjects answered "easy to use, " 20 (46.5%) answered "normal, " and six (13.9%) answered "difficult to use." Conclusions: The IcareHOME can be used as a self/home-tonometer; however, it may result in lower IOP values.